The Washback Effects of Arabic Language Final Examination Using the GeSchool Application - Robbani, A Syahid; Mirma, Afdhal Fikri; Munadi, Yudhi; S. Safa, Bilqis Salsabila; Badar, Sulmi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Assessment played a crucial role in developing learning behaviors, with both positive and negative impacts. This study examined the washback effects of the Arabic language final examination conducted through the GeSchool application from Madrasah Sumbar Blended Learning. The research was carried out during the 2021/2022 academic year with 141 twelfth-grade students at MA Muhammadiyah Lakitan, West Sumatra, Indonesia, of which 92 participants were selected using Isaac and Michael's sampling technique. A survey design was employed, with data collected through a self-report questionnaire, participant observation, and documentation. The 25-item questionnaire covered seven domains, including exam preparation strategies, learning attitudes, and instructional materials, and used a 5-point Likert scale. The instrument was validated using Pearson Product Moment Correlation, yielding valid results, while reliability testing produced a Cronbach’s Alpha score of 1.05. Descriptive statistical analysis showed that the mean scores for exam preparation strategies, learning attitudes, and instructional materials were 3.72, 3.81, and 3.79, respectively, categorized as